SGS-LTER long-term monitoring project: small mammals on trapping webs on the Central Plains Experimental Range, Nunn, Colorado, USA 1994 -2006, ARS study number 118 - Stapp, Paul (Colorado State University. Libraries, 1994)
This data package was produced by researchers working on the Shortgrass Steppe Long Term Ecological Research (SGS-LTER) Project, administered at Colorado State University. Long-term datasets and background information (proposals, reports, photographs, etc.) on the SGS-LTER project are contained in a comprehensive project collection within the Repository (http://hdl.handle.net/10217/100254). The data table and associated metadata document, which is generated in Ecological Metadata Language, may be available through other repositories serving the ecological research community and represent components of the larger SGS-LTER project collection. Small mammals (rabbits, rodents) are integral components of semiarid ecosystems because of their roles as consumers of plants, seeds and arthropods, as soil disturbance agents, and as food for raptors, snakes and mammalian carnivores. Because of their vagility and intermediate trophic position, populations of small mammals may track changes in vegetation and the abiotic environment that may result from shifts in land-use and other anthropogenic disturbances. However, these populations are variable over space and time, and their response to environmental changes may not be immediately apparent given their behavioral flexibility and relatively long life-spans and generation times. Patterns in the distribution and abundance of small mammals thus may simultaneously reflect and affect the stability of the shortgrass-steppe ecosystem. Long-term studies of population and community dynamics therefore are needed to fully understand the role of small mammals in grassland ecosystems. In 1994, we implemented a sampling scheme to monitor long-term changes in relative abundance of small mammals in representative habitats of shortgrass steppe. We live-trapped nocturnal rodents twice each year (spring, late summer) on trapping webs in upland prairie (GRASS) and saltbush-dominated (SHRUB) habitats. Three 3.14-ha webs were established in each habitat. Each web had 124 Sherman traps, which were spaced 10-m apart on 12 100-m spokes, with 30 degrees between spokes. Four traps were set in the center of the web. Traps were set for four consecutive nights in each trapping session. Traps are baited with a mix of peanut butter and oats, set in the evening and checked (and closed) at dawn. We recorded sex, age and weight upon first capture of all individuals. In the early years of the study, individuals were batch-marked (Sharpie colored felt markers) to distinguish recaptures from new individuals, providing the minimum information necessary to use distance-sampling methods to estimate density. Most nocturnal species are now usually marked with aluminum ear tags, although we continue to mark very small (pocket mice) or small-eared (voles) species only with felt pens. For ear-tagged animals, we distinguish new captures (N) from individuals marked during previous sessions (old, O), versus those that are recaptured (R) on 2nd, 3rd or 4th nights of a trapping session. The location of one trapping web was changed from 13NE (1994-1997) to 13SW (1998- present) because of concerns about intensive cattle use in the pasture, as well as activity of CPER Site Manager's cats.
The Short Grass Steppe site encompasses a large portion of the Colorado Piedmont Section of the western Great Plains. The extent is defined as the boundaries of the Central Plains Experimental Range (CPER). The CPER has a single ownership and landuse (livestock grazing). The PNG is characterized by a mosaic of ownership and land use. Ownership includes federal, state or private and land use consists of livestock grazing or row-crops. There are NGO conservation groups that exert influence over the area, particularly on federal lands.
Natural Resource Ecology Laboratory (NREL)
Shortgrass Steppe-Long Term Ecological Research (SGS-LTER)
Keywords: populations; mammals; population dynamics; community dynamics; shrublands; rodents; grasslands